Behavior of Ni(II) and Mn(II) in single and binary aqueous solutions in the adsorption process by rice hull ashes (RHA). Issue 15 (13th October 2017) - Sánchez-Flores, N. A.; Olguin, M. T.; Solache-Ríos, M.; Giron, P.; Bartolo-Pérez, P.; Pacheco-Malagón, G.; Bulbulian, S.
ABSTRACT: The retention of nickel and manganese by calcined rice hull ashes (RHA) in single and binary solutions was determined as a function of metal concentration and time. The maximum adsorptions of RHA for Ni(II) and Mn(II) were 7.27 and 6.45 mg/g from monocomponent solutions, and 4.6 and 3.8 mg/g from bicomponent solutions, respectively. The kinetic experimental data best fit a pseudo-second-order model. The k2 is higher for Mn(II) than Ni(II) considering the monocomponent solutions and this parameter is similar between them if the bicomponent solution is considered. The metallic species were partially desorbed from RHA by water.